Effect of Water-Cement Ratio on Flexural Strength of RC Beams Made with Partial Replacement of Coarse Aggregates with Coarse Aggregates from Old Concrete - Oad, M.; Buller, A. H.; Memon, B. A.; Memon, N. A.; Tunio, Z. A.; Memon, M. A. (Engineering, Technology & Applied Science Research, 2019)
This research paper presents an experimental evaluation of the effect of water-cement ratio on the flexural strength of reinforced concrete beams made with 50% replacement of coarse aggregates with recycled concrete aggregates (RCA). 72 reinforced concrete beams were cast using 0.54, 0.6, 0.65 and 0.70 water-cement ratio. In each ratio, 12 beams were cast using RCA and 3 beams were cast using all-natural coarse aggregates (NCA). Beams were cured for 7 and 28 days. After curing, all beams were tested with central point load in a universal load testing machine. From the obtained results, it is observed that the maximum reduction in flexural strength of RCA beams is about 28% when compared to the 0.54 w/c ratio beams of the same group and 31.75% in comparison to NCA beams cast with same w/c ratio. The maximum deflection and average strain in beams remained within limits. The observed cracking pattern shows shear failure of all beams.